Alzheimer's disease like pathology induced six weeks after aggregated amyloid-beta injection in rats: increased oxidative stress and impaired long-term memory with anxiety-like behavior. (1st September 2016) - Sharma, Sheetal; Verma, Sonia; Kapoor, Monika; Saini, Avneet; Nehru, Bimla
Abstract : Objectives : Amyloid-beta (Aβ) peptide deposition into insoluble plaques is a pathological hallmark of Alzheimer's disease (AD), but soluble oligomeric Aβ is considered to be more potent and has been hypothesized to directly impair learning and memory. Also, evidences from some clinical studies indicated that Aβ oligomer formation is the major cause for early AD onset. However, the biochemical mechanism involved in the oligomer-induced toxicity is not very well addressed. So, thise present study was undertaken to study the effects of single intracerebroventricular (icv) injection of protofibrillar Aβ 1-42 on the behavioral and biochemical profile in rats. Methods : Rats were divided into two groups ( n = 8 per group): (1) sham control group and (2) Aβ 1-42 injected group. A single dose of protofibrillar Aβ 1-42 (5 ul) through icv injection was bilaterally administered into the dorsal hippocampus, while sham control animals were administered with 5 µl of vehicle. Results : The results demonstrated that the protofibrillar Aβ significantly inhibited long-term memory retention and increased anxiety levels as shown by the behavioral studies. The amyloid deposits were present inside the brain even six weeks after injection as confirmed by thioflavin-T staining and the neurodegeneration induced by these deposits was confirmed by Nissl's staining in hippocampal and cortical regions. The amyloid aggregates induced reactive oxygen species (ROS) production, acetylcholinesterase activity, nitrite levels, lipid peroxidation, and inhibited antioxidant enzyme activity in hippocampus, cortex, and striatum regions of rat brain after six weeks. Discussion : The present study indicated that protofibrillar Aβ 1-42 injection altered long term memory, induced anxiety-like behavior and also developed Alzheimer's disease like pathology in rats. Abstract :